Changing Farmers' Perception towards Sustainable Horticulture: A Case Study of Extension Education in Farming Community in Yogyakarta, Indonesia - Epsi Euriga; Michael Henry Boehme; Siti Amanah (AGRARIS: Journal of Agribusiness and Rural Development Research, 2021)
Applying sustainable horticulture as an innovation in The Special Region of Yogyakarta (DIY) Indonesia can be a commendable example in agricultural extension education. Previous research has revealed that understanding farmers' perceptions of innovation is essential for appropriate interventions to change their behavior. In DIY, the surveys were conducted in 2016 with 257 males and 93 females of farmers groups member from 21 villages in Sleman, Bantul, and Kulonprogo Regency. The objective of the survey was to determine the effects of farmer's internal factors on the perception of ecological, social economy, and ethical (ESE) urgency as a component of sustainable horticulture practices. The findings from the ecological, social, and ethical dimensions among the farming community in DIY indicated that, directly and indirectly, the farmers can acknowledge and practice sustainable horticulture. However, this was altering several factors, most notably, motivation and the prospect of increased income. The important thing in extension work was motivation, and a major motivating factor was the possibility of increased agricultural income. This study suggests that extension education of achieving horticultural sustainability in DIY should be based on the motivation of farmers and thoughtfulness of their basic needs especially needs to have higher income.